A Review of Acupuncture Treatment for Infertility - Hea sun Chun; Ho-Sueb Song (MEDrang Inc., 2021)
The purpose of this study was to analyze acupuncture treatment methods and acupoint used to treat infertility in the last decade. The data were retrieved from 2010.1 to 2021.8. using national and international electronic databases (PubMed, EMBASE, OASIS, NDSL, and KISS). "Infertility," "sterility," "acupuncture," "electroacupuncture," "bloodletting," "pharmacopuncture," were used as search terms. All studies were mainly concerned with acupuncture treatment of infertility, but the studies which were not related included; (1) infertility or acupuncture treatment; (2) animal studies; (3) review/meta/protocol or clinical study; comparative studies and case reports which were excluded from this review. Only clinical trials for acupuncture treatment of infertility were included in this review (n = 18). For infertility treatment studies using acupuncture, polycystic ovarian syndrome was the main cause of infertility, the most common acupoint used was CV4, CV3, CV6, SP6, BL23, and the treatment effect significantly improved in the group receiving acupuncture treatment compared with the control group, or the group taking Western medicine alone. In some studies, the group using acupuncture treatment did not show side effects. Acupuncture is an effective treatment for infertility.